2018
DOI: 10.1002/brb3.1009
|View full text |Cite
|
Sign up to set email alerts
|

Impact of brain‐derived neurotrophic factor genetic polymorphism on cognition: A systematic review

Abstract: IntroductionBrain‐derived neurotrophic factor (BDNF) has an important role in the neurogenesis and neuroplasticity of the brain. This systematic review was designed to examine the association between BDNF Val66Met (rs6265) polymorphism and four cognitive domains—attention and concentration, executive function, verbal fluency, and memory, respectively.MethodologyPrimary literature search was performed using search engines such as PubMed and Scopus. Observational studies that evaluated the neurocognitive perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
46
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(62 citation statements)
references
References 95 publications
8
46
2
2
Order By: Relevance
“…Since the SNPs of MCT8, MCT10 and DIO2 are crucial for the function of thyroid hormones, we were interested if they would also influence cognitive functions and personality traits. There are numerous instances in which an influence of polymorphisms, mostly in monoaminergic genes, on both, cognitive processes [38][39][40][41] and personality traits [42][43][44][45] has been shown which motivated our approach. Previous studies have also shown that the amount of variance that can be explained by single polymorphisms is rather modest.…”
Section: Introductionmentioning
confidence: 99%
“…Since the SNPs of MCT8, MCT10 and DIO2 are crucial for the function of thyroid hormones, we were interested if they would also influence cognitive functions and personality traits. There are numerous instances in which an influence of polymorphisms, mostly in monoaminergic genes, on both, cognitive processes [38][39][40][41] and personality traits [42][43][44][45] has been shown which motivated our approach. Previous studies have also shown that the amount of variance that can be explained by single polymorphisms is rather modest.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, a study using an auditory distraction paradigm-different, methodologically, from standard cognitive testing-has shown that BDNF Val homozygosity may be disadvantageous when inhibitory mechanisms are required, indicating that increased activation associated with the Val allele may not be advantageous for inhibitory effects processed in frontal pathways [40]. A recent systematic review on the topic has confirmed that BDNF Val66Met likely has some impact on cognitive function, although the specific direction is difficult to ascertain [41]. Additionally, Toh and colleagues [41] suggest that Met may be advantageous for executive functioning, although broader results are not consistent.…”
Section: Bdnf Val66met and Cognitive Functionmentioning
confidence: 99%
“…A recent systematic review on the topic has confirmed that BDNF Val66Met likely has some impact on cognitive function, although the specific direction is difficult to ascertain [41]. Additionally, Toh and colleagues [41] suggest that Met may be advantageous for executive functioning, although broader results are not consistent.…”
Section: Bdnf Val66met and Cognitive Functionmentioning
confidence: 99%
“…BDNF promotes survival and functions of neurons. In AD, BDNF mRNA, and protein levels were found to be decreased, possibly contributing to memory deficits and neuronal loss (reviewed in Toh, Ng, Tan, Tan, & Chan, 2018;Zhao et al, 2017). Similarly, BDNF expression is lowered in neurodegenerative conditions with Tau pathology (Belrose, Masoudi, Michalski, & Fahnestock, 2014).…”
Section: Bdnf Signalling In Admentioning
confidence: 99%